2021
DOI: 10.7759/cureus.15383
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostically Challenging Parotid Gland Tumor With Hybrid Features

Abstract: Salivary gland tumors are relatively uncommon with most being benign. When diagnosed the most common benign and malignant tumors are pleomorphic adenoma and mucoepidermoid carcinoma (MEC), respectively. However, not uncommonly, it is difficult to differentiate between the histopathological entities, leading to a diagnostic dilemma that can impact a patient's treatment and prognosis. A 24-year-old woman presented with a three-year history of asymptomatic left-sided facial swelling. She denied any prior history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These tumors are often high-grade and invasive. 4 In the literature we have accessed in the last 20 years, we have compiled Table 1 summarizing case reports that raise suspicion of malignant salivary gland tumors due to widespread metaplastic changes in the PA. 1,[6][7][8][9][10][11][12][13][14] In this case, a prior FNAB performed elsewhere prompted the excision of the lesion. While evaluating fine needle aspiration biopsies of pleomorphic adenomas can be challenging due to their diverse metaplastic components, the Milan reporting system may place such aspirates in risk categories (III, IVA, IVB, V, or even VI).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These tumors are often high-grade and invasive. 4 In the literature we have accessed in the last 20 years, we have compiled Table 1 summarizing case reports that raise suspicion of malignant salivary gland tumors due to widespread metaplastic changes in the PA. 1,[6][7][8][9][10][11][12][13][14] In this case, a prior FNAB performed elsewhere prompted the excision of the lesion. While evaluating fine needle aspiration biopsies of pleomorphic adenomas can be challenging due to their diverse metaplastic components, the Milan reporting system may place such aspirates in risk categories (III, IVA, IVB, V, or even VI).…”
Section: Discussionmentioning
confidence: 94%
“…2 Metaplastic changes in PA may be diagnostically challenging and cause pitfalls in the diagnosis of fine needle aspirations particularly in the absence of chondromyxoid stroma. 3,5,6 The potential misinterpretations of malignancy are made, especially for MEC. 5 Brachtel et al reported that misinterpretation may lead to over-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Common contraindications include patients with malignant or recurrent parotid gland tumors or a history of neck surgery or radiation therapy. 25,26 In addition to improving cosmetic results, the use of these incisions can reduce the incidence of postoperative complications such as temporary and permanent facial paralysis, salivary fistulas, facial depression, and Frey syndrome by reducing damage to the great auricular nerve and incidence of earlobe numbness. Additionally, most of these methods avoid hairline incisions, so the incidence of hypertrophic scarring and hair loss is significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The main indications for these minimally invasive surgeries with cosmetic incisions are superficial or partial parotidectomy for small BPTs (usually <4 cm). Common contraindications include patients with malignant or recurrent parotid gland tumors or a history of neck surgery or radiation therapy 25,26 …”
Section: Discussionmentioning
confidence: 99%